Gender & caste - Rao, Anupama; Kali for Women (Organization); Book Review Literary Trust (New Delhi, India) (New Delhi : Kali for Women in association with the Book Review Literary Trust, 2003)
Contributed articles on the issues related to Dalit women in India.
Keywords: Poor women -- India; Dalits -- India; Women -- India -- Social conditions; Caste -- India; Feminism -- India